Electronic Properties of (111) Surface in A3B5 and A2B6 Crystals - Gorkavenko, T.V.; Zubkova, S.M.; Makara, V.A.; Rusina, L.N.; Smelyansky, O.V. (Ukrainian Journal of Physics, 2022)
The electronic band structure, the local densities of states (the total and layer-resolved ones), and the distribution of charge density of valence electrons at the (111) polar surface in A3B5 and A2B6 crystals, such as GaAs and ZnSe, have been studied. The properties of anion- and cation-terminated surfaces have been analyzed separately. The self-consistent ``3D’’ pseudopotential method has been used for numerical calculations in the framework of a model of layered superlattice. The application of an original iterator in the self-consistence procedure allowed difficulties associated with the surface-induced presence of reciprocal-lattice vectors shorter that 1 a.u. to be overcome.